Peran komunitas penulis dalam meningkatkan kemampuan literasi menulis pada Guru Perguruan Muhammadiyah Salatiga - Marwanto, Marwanto; Widyastuti, Widyastuti (Nur Science Institute, 2024)
The role of teachers in literacy is very dominant for students. Teachers are an inseparable example. They must be able to express their thoughts in writing and reflect on their teaching experience to students. The purpose of this study is to find out the role of the author community in improving the literacy ability of Muhammadiyah Salatiga teachers. This research is qualitative descriptive. The population in this study is Muhammadiyah Salatiga teachers. This method utilizes interview, observation, and documentation techniques. This research results in Progressive Teachers who have learned writing literacy with the guidance of a mentor. In improving the quality of literacy, they were all given target results in the form of writing that had to be shared in the group and then corrected by group members and mentors. The Progressive Teacher Community has several roles for each member: active writers, corrective, sharing knowledge and references, motivating group members, and producing or publishing books. Progressive Teachers get benefits that can be felt with the writing community, namely learning together, various information, improving writing skills, motivating or supporting each other, writing anthologies or simultaneously, and relationships and friendships.